2012
DOI: 10.1080/00343404.2012.678824
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Economic Growth in European Regions

Abstract: We use Bayesian Model Averaging (BMA) to evaluate the robustness of determinants of economic growth in a new dataset of 255 European regions in the 1995-2005 period. We use three different specifications based on (1) the cross-section of regions, (2) the cross-section of regions with country fixed effects and (3) the cross-section of regions with a spatial autoregressive (SAR) structure. We investigate the existence of parameter heterogeneity by allowing for interactions of potential explanatory variables with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
85
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(97 citation statements)
references
References 51 publications
4
85
0
1
Order By: Relevance
“…In addition, the literature on the impact of human capital and innovation on economic development and growth in the European regions is also large (e.g., Fagerberg, Verspagen, and Caniels 1997;Rodríguez-Pose and Crescenzi 2008;Sterlacchini 2008;Cuaresma, Doppelhofer, and Feldkircher 2012). For example, Badinger and Tondl (2003) investigate whether human capital and innovation (as measured by patent applications) have a significant impact on the growth rates of Gross Value-Added per capita in 128 regions between 1993 and 2000.…”
Section: Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the literature on the impact of human capital and innovation on economic development and growth in the European regions is also large (e.g., Fagerberg, Verspagen, and Caniels 1997;Rodríguez-Pose and Crescenzi 2008;Sterlacchini 2008;Cuaresma, Doppelhofer, and Feldkircher 2012). For example, Badinger and Tondl (2003) investigate whether human capital and innovation (as measured by patent applications) have a significant impact on the growth rates of Gross Value-Added per capita in 128 regions between 1993 and 2000.…”
Section: Literaturementioning
confidence: 99%
“…Moreover, Sterlacchini (2008) finds that human capital (in the form of higher education) and a region's knowledge base have a significant and positive impact on economic growth in twelve EU15 countries between 1995 and 2002. Cuaresma, Doppelhofer, and Feldkircher (2012) use a dataset including 255 EU regions to analyse which of their 48 potential determinants are significantly explaining economic growth between 1995 and 2005. Two of their most important results are that capital regions grow faster than other regions and that human capital (i.e., higher education) is a robust determinant of economic growth.…”
Section: Literaturementioning
confidence: 99%
“…As a result, they were able to confirm a significant influence of the quality of human capital on the level of TFP in the new EU member states. �oreover, Cuaresma et al (2014) showed that the regions around the capitals of the new members of the EU grew rapidly because of more educated labour resources in 1995-2005. In the context of competitive potential in the reality of knowledge based economy, the role of research and development investments (R&D) is also often taken into consideration (Bilas et al, 2016). In spite of the fact that the R&D expenditure is commonly treated as the most important investment in building knowledge based economy -the need for increasing the scale of investments in this field in all European countries up to 3% of GDP was the most recognised agenda of Lisbon Strategy and is also included in Europe 2020 strategy -the empirical research shows that that the influence of R&D on the growth process is very complex.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the earliest prominent theories explaining economic growth is neoclassical theory (Solow, 1956;Swan, 1956), which identifies investment in physical capital and labor as the key driver of growth. Many subsequent studies have identified other factors such as technological progress or innovation, government consumption, trade and trade terms, political stability, income distribution, inflation, the rule of law, and fertility (Barro, 1996;Chen & Feng, 2000;Anaman, 2004;Cuaresma, Doppelhofer, & Feldkircher, 2014;Vedia-Jerez & Chasco, 2016;Barro, 1991;Qayum, 2005;Vedia-Jerez & Chasco, 2016;Persson & Tabellini, 1992). All of these studies have confirmed the so-called conditional convergence of firms and nations (Evans & Karras, 1996;Quah, 1996).…”
Section: Technological Determinants Of Economic Growthmentioning
confidence: 93%